2013
DOI: 10.1002/clen.201200152
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Benthic Diatoms and Water Quality Assessment Using Diatom Indices in a Subtropical River, China

Abstract: River systems constitute areas of high human population densities owing to their favourable conditions for agriculture, water supply and transportation network. Despite human dependence on river systems, anthro-pogenic activities severely degrade water quality. The main aim of this study was to assess the river health of Ngamo River using diatom and macroinvertebrate community structure based on multivariate analyses and community metrics. Ammonia, pH, salinity, total phosphorus and temperature were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
(66 reference statements)
2
18
0
Order By: Relevance
“…In addition to nutrient availability, water flow was also identified as an important factor in structuring diatom communities in this study, which again is consistent with previous studies conducted both locally and internationally (e.g. Ruth, 1977;Biggs et al, 2005;Song, 2007;Tan et al, 2014b;Bere et al, 2013;Dalu et al, 2014a).…”
Section: Physico-chemical Factors Influencing Diatom Communitiessupporting
confidence: 92%
See 4 more Smart Citations
“…In addition to nutrient availability, water flow was also identified as an important factor in structuring diatom communities in this study, which again is consistent with previous studies conducted both locally and internationally (e.g. Ruth, 1977;Biggs et al, 2005;Song, 2007;Tan et al, 2014b;Bere et al, 2013;Dalu et al, 2014a).…”
Section: Physico-chemical Factors Influencing Diatom Communitiessupporting
confidence: 92%
“…land use and/or cover) likely also influenced the benthic diatom community structure and distribution in the Kowie River system. Tan et al (2014b) also observed similar findings in the Han River, where he suggested that factors such as substratum, ultimate factors (i.e. land use) and biological pressure such as predation (i.e.…”
Section: Physico-chemical Factors Influencing Diatom Communitiesmentioning
confidence: 56%
See 3 more Smart Citations